Harvesting resilience: Community perspectives on early warning systems in Ethiopia - Walker, Aurelie; SheikhBihi Adam, Abdulfatah (Urban Foresight, 2025)
Presented at the Jameel Observatory drylands food security and resilience early action research and evidence dialogue, Addis Ababa, Ethiopia, 15-16 May 2025